Bi−P Bond Homolysis as a Route to Reduced Bismuth Compounds and Reversible Activation of P4. Issue 47 (26th October 2016) - Schwamm, Ryan J.; Lein, Matthias; Coles, Martyn P.; Fitchett, Christopher M.
Abstract: Bismuth diphenylphosphanides Bi(NON R )(PPh2 ) (NON R =[O(SiMe2 NR)2 ], R= t Bu, 2, 6‐ i Pr2 C6 H3, Aryl) undergo facile decomposition via single‐electron processes to form reduced Bi and P species. The corresponding derivatives Bi(NON R )(PCy2 ) are stable. Reaction of the isolated Bi II radical . Bi(NON Ar ) with white phosphorus (P4 ) proceeds with the reversible and selective activation of a single P−P bond to afford the bimetallic μ, η 1:1 ‐bicyclo[1.1.0]tetraphosphabutane compound. Abstract : The stability of terminal Bi−P bonds in diamidobismuth(III) phosphanides towards single‐electron decomposition depends on the phosphorus ligands. Diphenylphosphanides spontaneously decompose to Bi II species, used to prepare a new diamidodibismuthane and exploited in the reversible activation of P4 by an isolated Bi II radical (see scheme), whereas dicyclohexylphosphanides can be isolated.